Study on the nonlinear deformation and failure mechanism of a high arch dam and foundation based on geomechanical model test. (15th March 2020) - Tao, Zhuofu; Liu, Yaoru; Yang, Qiang; Wang, Shouguang
Highlights: Geomechanical model test based on masonry method for failure analysis of arch dam. Comparing and verifying the results of model test and numerical calculation. Deformation and failure evolution of dam-foundation during overloading process. Analogy analysis of model test results of several different arch dams. Failure of dam toe is the change point of nonlinear deformation. Abstract: Mengdigou double-curvature arch dam, located in the southwest of China, is a 200-meter-high dam with complex geological conditions. Failure analysis of the arch dam coupled with the foundation is important for evaluation of the stability. In this regard, a geomechanical model test was carried out. The data pertaining to displacements, stresses, and acoustic emissions, and the entire process of the failure occurring during overloading were obtained. During the overloading process, crack initiates in the upstream dam heel. Then, a crack appears downstream at the dam toe as the load increases. After the damage of the dam toe, cracks occur in the faults around the abutment. Meanwhile, cracks develop rapidly in the arch dam. Eventually, the dam-foundation system loses its ultimate bearing capacity and fails. The results of the model test were compared with those of numerical calculation. Then, the nonlinear deformation and failure mechanism was analyzed. Finally, the safety factor of cracking of the arch dam, the safety factor of the initial nonlinear deformation, and the safety factor of the ultimate bearing capacity were obtained, which reveal that the design of the arch dam is reasonable.